Water for whom? Community mobilization and negotiation during socio- environmental conflict in Parque Los Chorros, Costa Rica - María Stephanie Valenciano-Hernández (Íconos)
Unplanned urban growth in Costa Rica has resulted in a disproportionate expansion of existing cities. A chaotic situation has resulted from this and the real estate industry is often blamed. In its shortsighted search for easy profits, this sector of the economy is accused of developing new housing projects without previous adequate planning of basic service provision. This has been happening in Atenas County in Alajuela province. Here the growing population has been denied an adequate access to water. In an attempt to solve this problem, the administration implemented a project to provide water to be taken from sources in a nearby community. This triggered a dispute over the control of the water sources, which confronted Government institutions and the Atenas and Tacares communities. This article focuses both in the dispute itself and in Government-led attempts to find a negotiated solution to the conflict. A qualitative research design is used, including semi-structured interviews with both local Tacares community and institutional actors. Documentary research into official records and into local and international media reports is also performed. In the end, the article reaches the conclusion that throughout the conflict, power asymmetries between the different actors were reproduced. The research also allowed to highlight the fact that community and social participation in decision-making is only promoted once conflicts seriously escalate.